The contribution of income from Non Timber Forest Product to the agroforestry business in community forest in Tasikmalaya Regency - Dian Diniyati; Budiman Achmad (Jurnal Ilmu Kehutanan)
Community forests is not merely producing timbers, but also non timber forest products (NTFPs) which are even more important at several places. The objective of the research was to obtain the data with regard to the advantage of developing NTFPs from community forests and its contribution to income of farmer. This study was conducted at Karyamukti village, Parungponteng Sub-district, Tasikmalaya District from June to December 2013. Thirty forest farmers were selected by stratified random sampling technique based on the size of forest ownership. Questioners were used to support interviews during data collection activities. Collected data were statistically analyzed and presented descriptively. The result showed that respondents own land areas averagely 0.374 ha whereas 0.246 ha or 65.78 % of them were utilized for community forest business. The developed planting system was agroforestry i.e. mixing the timber plants with NTFP plants such as estate, fruity, medicinal, and food plants. The period income gained from NTFP could be weekly, monthly, and annually. Income contributions of NTFPs to total income from farm forest were 67.56 % (level 1), 63.93 % (level 2) and 75.11 % (level 3), while the income contributions of timbers were only 32.44 % (level 1), 36.07 % (level 2), and 24.89 % (level 3). The annual income contribution of NTFPs, therefore, was higher than the one from timbers. The contribution, actually, could be increased if the NTFPs were developed seriously. One constrain in the NTFPs development was the silviculture technique operated by farmers, which did not follow the standard operational procedure (SOP) issued by The Ministry of Agriculture. Based on that condition, efforts to improve NTFPs development by transferring the knowledge and technology through extension are urgently required.